Evaluation of oraquick® HIV-1/2 as oral rapid test - Nkenfou, C.N.; Kembou, J.E.; Temgoua, E.S.; Djikeng, Appolinaire; Mouafo, L.M.; Ndzie, E.N.; Donkam, I.; Colizzi, V.; SanouSobze, M. (African Journals Online, 2013)
As Cameroon scales up its national HIV/AIDS control program, evaluating the performance of commercially available tests for accurate and cost effective diagnostics becomes essential. A cross-sectional study assessed the performance of an HIV oral rapid test. A total of 1520 participants consented to participate in the study. After counselling, they were tested for HIV using the national algorithm followed by OraQuick. Results of the national algorithm were compared to those of OraQuick, for sensitivity, specificity, positive predictive and negative predictive values. 62% of participants were male, and 1% was reported HIV-positive following the national algorithm. The OraQuick test had 93% sensitivity, 99% specificity, 99.93% NPV and 90% PPV (95% CI, Kappa 0.965). Though more expensive (2-6x) compared to the national algorithm tests, oral mucosal transudate-based test demonstrated good performance. Therefore, it could be implemented in resource constrained settings if subsidized and could increase participation since less invasive with no blood accident exposure.